2020
DOI: 10.1038/s41433-020-1019-5
|View full text |Cite
|
Sign up to set email alerts
|

Red reflex examination in reproductive and child health clinics for early detection of paediatric cataract and ocular media disorders: cross-sectional diagnostic accuracy and feasibility studies from Kilimanjaro, Tanzania

Abstract: Background/objectives Late presentation of congenital cataract in the developing world has led to poor outcomes such that cataract is the leading cause of childhood blindness. Our hypothesis was that, sensitivity of red-reflex testing is greater than sensitivity of torchlight examination. We aimed to compare sensitivity of new red reflex screening tools and assess the feasibility of Arclight red reflex screening in the community. Subject/methods We compared the diagnostic accuracy of four different screening t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 21 publications
0
20
0
2
Order By: Relevance
“…The results revealed a significantly higher rate of prompt diagnosis of pediatric cataract, when RRT was performed at maternity wards, in comparison with the absence of RRT. A survey in Tanzania concluded the same results[ 38 ]. The need for implementation of red reflex screening is even stronger in Turkey, the Middle East, Asia and Africa.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…The results revealed a significantly higher rate of prompt diagnosis of pediatric cataract, when RRT was performed at maternity wards, in comparison with the absence of RRT. A survey in Tanzania concluded the same results[ 38 ]. The need for implementation of red reflex screening is even stronger in Turkey, the Middle East, Asia and Africa.…”
Section: Resultsmentioning
confidence: 56%
“…The performance of the RRT, from infancy and at every well child visit, following current pediatric guidelines could prevent childhood blindness[ 3 , 38 ]. Literature data correlated the RRT with early detection of congenital cataract.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-ophthalmic staff who provide care to children, such as pediatricians, staff delivering immunisation programmes and neonatal/obstetric nurses could be trained to perform the BRT both opportunistically and systematically in their daily work. The feasibility of this approach has recently been evaluated in Tanzania demonstrating the Arclight to have sensitivity and specificity of over 90% (15). This could lead to earlier identification of eye conditions benefiting from intervention potentially improving outcomes of treatment and reducing the burden of visual impairment in children.…”
Section: Discussionmentioning
confidence: 99%
“…We are aware of one study in Tanzania which is in press and another unpublished study in Nigeria in which nurses were trained to elicit the red reflex of children to detect eye conditions such as cataract. 15 In one study three devices were assessed, one of which was the Arclight. Both studies demonstrated that nurses can correctly and reliably undertake this screening test (personal communications).…”
Section: Discussionmentioning
confidence: 99%